Communicative Language Teaching to develop oral production on intermediate level students at Sucre Language Institute in Quito - Nato Sierra, Carmen Elisa (2023)
To determine the efficiency of using the Communicative Language Teaching activities in the development of oral production on intermediate-level students at Sucre Language Institute of Quito in the academic year 2021- 2022.